2019
DOI: 10.18502/jnfs.v4i2.768
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fast Food Consumption Based on Prototype/Willingness Model among Students of Yazd University of Medical Sciences

Abstract: Background: Consumption of fast food, as a consequence of the modern industrial society, has increased in recent years among teenagers and young people. The purpose of this study was to investigate the effect of fast food consumption on female students in Yazd University of Medical Sciences based on the Prototype/Willingness Model. Methods: In this descriptive-analytic study, 245 female dormitory students were selected from Yazd University of Medical Sciences by stratified sampling from six dorms. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The result of our study is in line with the findings of Mazloomy Mahmoodabad et al . that reported Intention to non-consumption of fast foods had a positive significant correlation with subjective norms, attitude, willingness, and prototype of fast food consumption 22 That shows more positive attitude and subjective norms of fast-food consumption is accompanied by more intention of consuming fast foods and showing more of the behavior.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The result of our study is in line with the findings of Mazloomy Mahmoodabad et al . that reported Intention to non-consumption of fast foods had a positive significant correlation with subjective norms, attitude, willingness, and prototype of fast food consumption 22 That shows more positive attitude and subjective norms of fast-food consumption is accompanied by more intention of consuming fast foods and showing more of the behavior.…”
Section: Discussionmentioning
confidence: 78%
“…entitled Predictors of Fast Food Consumption Based on Prototype/Willingness Model showed that intention to consumption of fast foods had a negative significant association with subjective norms, attitude, willingness, and prototype of fast food consumption. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Diet changes are interventions which entail conscious and subconscious expectations and beliefs ( 56 58 ). Generally, we can motivate ourselves to changes especially if we expect an improvement of the existing situation, as illustrated by models such as the Health Belief Modell ( 59 ), the Transtheoretical Model ( 60 ), the Prototype/Willingness Model ( 61 , 62 ), and the Health Action Process Approach ( 63 ). As a rule, individuals change their diet because they have expectations, e.g., health-promoting, weight-reducing effect, and/or appreciation from the social environment.…”
Section: Hypotheses On Classical Placebo and Nocebo Effects In Diet C...mentioning
confidence: 99%